A computational framework for irreversibility analysis in chemically reactive viscous hybrid nanofluid flow with heat source and thermal radiation - Rahman, Mujeeb ur; Khouqeer, Ghada A.; Haq, Fazal; Sallah, Mohammed (Journal of thermal analysis and calorimetry, 2025)
Entropy generation (EG) due to its applications in the industrial sector has turned into an attractive research area. Applications of EG frequently occur in air conditioners, chillers, air coolers, refrigerators, and all types of vehicle engines. Due to such extensive applications, the current study is focused on evaluating EG in the chemically reactive viscous flow of single-particle nanofluid (SPNF) and hybrid nanofluid (HNF) by a permeable stretchable sheet. Darcy–Forchheimer's relation is deliberated while reporting the momentum equation. Rigid nanoparticles of aluminum oxide Al 2 O 3 and copper Cu are suspended in water to form single-phase nanofluid ( Al 2 O 3 / H 2 O ) and hybrid nanofluid ( Al 2 O 3 - Cu / H 2 O ) . Dissipation, radiation, and heat source impacts are accounted in the expression for thermal energy. Chemical reaction impact is accounted in relation to concentration. The EG is modeled by the second law of thermodynamics. Through transformation, the partial differential equations (PDEs) representing the flow are altered into ordinary ones. To solve the ordinary system, the NDSolve function of Mathematica is utilized. Important variables impression on velocity, Bejan number, concentration, temperature, and EG for both single-particle nanofluid and HNF are analyzed graphically. Engineering quantities are inspected numerically. Results reveal that the temperature field of SPNF and HNF upsurges for higher radiation parameter while it decays for raising the Prandtl number. Concentration diminished for an upturn in chemical reaction and Schmidt number. EG is more for greater diffusion, temperature difference ratio, and Brinkman variables. Bejan number escalates for increasing diffusion and temperature difference ratio variables while it decays for up surging values of Brinkman variable.